KONTINUITAS DAN DISKONTINUITAS AL-QUR'AN TERHADAP TRADISI ARAB PRA-ISLAM - Kurdi (JURNAL PENELITIAN, 2015)
This article discusses on continuity and discontinuity of the Qur'an to Arabs traditions before revelation provided from either doctrine of prior religions or native agreements of society. The Qur'an has given response on many aspects of rituals, economy, family, law and punishments. Many of such traditions become as Islamic doctrine and others are rejected. The steps of the continuity are total acceptance, distinctive way, conditional limitation and corrective response, while the styles of the discontinuity are total, gradual and continuous liberations.